Податкове стимулювання діяльності малого бізнесу як напрямок подолання труднощів економічного розвитку держави - Мелень, Олена Валентинівна; Коваленко, О. В. (Видавничий дім "Гельветика", 2023)
У статті розглянуто питання податкового стимулювання малого бізнесу, як напрямку подолання труднощів економічного розвитку держави, оскільки він є основним джерелом економічного розвитку держави. Малий бізнес має неабияке значення для економіки України, тому однією з основних цілей сьогодення має бути підтримка малих суб’єктів підприємництва, які страждають через війну. Скорочення кількості підприємств та зниження темпів реєстрації нових бізнесів призведе до погіршення економічного становища держави. Стимулювання підприємницької діяльності України продиктовано прагненням економічного зростання та його соціальною направленістю. Підтримка малого бізнесу, в тому числі й через систему оподаткування, є одним із способів подолання економічної, політичної та соціальної криз в країні.

Small business is the main source of economic development of the state. It quickly responds to changes in the market environment, using new technologies and changing public needs. It practically does not require a large amount of start-up capital, ensures turnover of resources and quickly reacts to changes in the market structure, ensures overcoming of many socio-economic issues, etc. Therefore, one of the main tasks of the state is to support and stimulate the entrepreneurial activity of small business entities. Tax legislation of Ukraine is one of the most complex in the legal system of Ukraine. There is a trend towards its instability. As the practice of its enforcement shows, changes made to the laws of Ukraine on taxation often cause new problems. With the outbreak of full-scale war from February 24, 2022, existence and mood of small and medium-sized businesses worsened. Subjects of small and medium-sized enterprises consider the economic situation in the country to be very difficult. As a result of the hostilities, difficulties arose in lending to small businesses, logistics became more complicated, demand for products decreased, businesses were partially or completely suspended, and interruptions in electricity supply and communications also had a negative impact. Small business operating during the war is very important for the economy of Ukraine, therefore one of the main and priority tasks today is the support of small business entities. The state should respond more promptly to the needs of small business, develop and implement additional incentives for its recovery and further effective existence. Starting from 2022, important changes were made to the tax legislation in Ukraine, which relate to the stimulation and restoration of small entrepreneurship. In addition, various other stimulating factors have been introduced to support entrepreneurs, such as grants, loans and various projects of international donors. The changes in the tax legislation are aimed at reducing the tax pressure on business, improving the conditions for the development of entrepreneurship in the conditions of war, and thereby ensuring a more efficient receipt of taxes into the budget.
Tax incentives of small business activities as a direction for overcoming the difficulties of economic development of the state
Keywords: малий бізнес; податкове стимулювання; спрощена система оподаткування; єдиний податок; державна політика; small business; tax stimulation; simplified taxation system; unified tax; government policy